TLR4 receptor expression and function in F11 dorsal root ganglion × neuroblastoma hybrid cells. Issue 8 (November 2017) - Hashemian, Sanaz; Alhouayek, Mireille; Fowler, Christopher J
TLR4 respond to bacterial LPS to produce inflammatory cytokines. TLR4 are expressed in dorsal root ganglia and play a role in pain. F11 dorsal root ganglia × mouse neuroblastoma cells possess many of the properties seen in nociceptive dorsal root ganglia neuronal cells. Here, we investigated the effect of 2 h and 6 h treatment with LPS upon the expression of inflammatory proteins in undifferentiated and differentiated F11 cells. The cells expressed mRNA for TRL4 (mouse, not rat) and proteins involved in TLR4 signaling. TLR4 expression was confirmed using immunohistochemistry. LPS produced modest increases in mouse and rat IL-6 and in mouse cyclooxygenase-2 levels in undifferentiated cells, but did not significantly affect mouse TNF-α expression. This contrasts with the robust effects of LPS upon cyclooxygenase-2 expression in cultured dorsal root ganglia neurons. F11 cells expressed the endocannabinoid metabolizing enzymes fatty acid amide hydrolase and N -acylethanolamine acid amidase (both murine), which were functionally active. These data suggest that F11 cells are not a useful model for the study of LPS-mediated effects but may be useful for the study of endocannabinoid catabolism.